Conceptual Development of a Personalized Learning System for Type 2 Diabetes Mellitus Prevention. (September 2014) - Davis, Dorian; Jiang, Steven
Advancing personalized learning has been identified as one of the grand challenges by the National Academy of Engineering. It is an approach that customizes the delivery of information based on different learning groups. Personalized learning provides choices and flexibility in how, what, when and where we learn. It also allows the user of the system to actively participate in the development of their learning. This re-search aims to study personalized learning designed for preventive care of Type 2 Diabetes Mellitus Health Information System. User-centered design will be applied during the design process. A framework will be developed for the design of a personalized system that individually adapts to learning styles.